Skeletal age and biological maturity in Japan Professional Soccer League U15 category players - Takahara, R.; Miyakawa, S. (The Journal of Physical Fitness and Sports Medicine, 2020)
One method of determining a person`s biological maturity involves evaluating their bone maturity. Differences in physical abilities among athletes during the growth period are thought to be strongly influenced by differences in bone maturity. Thus, it is necessary to understand biological maturity when selecting athletes. Accordingly, this study looks at the biological maturity of young Japanese soccer players in the Japan Professional Soccer League. In total, subjects included 282 male soccer players (mean age, 12.4 ± 0.7 years; mean height, 154.0 ± 9.1 cm) in the J-League Academy, 2007-2012. Results show that the TW2-RUS method (Japan) revealed no significant difference (t = 1.012, df = 277, ns); however, the TW3-RUS method revealed a significant difference (t = -4.075, df = 281, p < 0.05) for chronological age vs skeletal age in t-test. The breakdown of biological maturity according to the TW2-RUS method (Japan) was as follows: mature, 3 persons; early maturing, 45 persons; average, 196 persons; and late maturing, 38 persons. The breakdown of biological maturity according to the TW3-RUS method was as follows: mature, 3 persons; early maturing, 53 persons; average, 132 persons; and late maturing, 94 persons. The chi-square test revealed a significant difference (p < 0.001) between the TW2-RUS method (Japan) and the TW3-RUS method. Our results suggest that it is appropriate to use the TW2-RUS method (Japan) to evaluate skeletal age. With regard to biological maturity, contrary to prior research in Europe and America, a high proportion of our athletes had average biological maturity.